Borrowing From Sleep to Pay Work and Family: Expanding Time-Based Conflict to the Broader Non-Work Domain - BARNES, C. M. (Institutional Knowledge at Singapore Management University, 2012)
We extend cross-domain research by examining sleep, a domain within the larger nonwork domain that competes for time with work and family domains. We draw from scarcity theory and research on slack resources to contend that, because people cannot increase the amount of time they have, they borrow time from sleep in order to spend more time working and with family. Utilizing a Bureau of Labor Statistics survey of 10,741 participants, we find nonlinear and interactive effects of time spent working and time spent with family on sleep time, suggesting that the negative effects of work and family on sleep time are especially strong when demands for work and family are high. In an experience sampling field study of 122 working adults, we similarly find a nonlinear effect of work time on sleep time as well as an interaction between work time and family time in predicting time spent sleeping. Both studies indicate that as slack time resources become increasingly scarce, time spent working and time spent with family have increasingly powerful negative effects on time spent sleeping. Contrary to our expectations, we found no support for gender as a moderator of these effects